SOSIALISASI PEMBUATAN HANDSANITIZER DAN PEMBAGIAN MASKER DI KELURAHAN LASIANA - Diana Yani Fallo; Roswita Lioba Nahak; Santi Frans; Fitriani Tefa; Yunvi Mbait; Arjelita Bete; Inggrit Roman (FKIP Universitas Citra Bangsa, 2021)
This community service was held at SDK Assumpta which is located in Lasiana village, Kelapa Lima Subdistrict, Kupang City, and along the road to the Oebobo bus terminal parking lot. This service was carried out by Informatics Education and PGSD lecturers as well as FKIP students of Citra Bangsa University. This kind of activity was conducted online and offline. There were two kinds of activities done, that is to say, hand sanitizers manufacture and mask distribution. Hand sanitizer manufacture was done online, while community service and data collection on citizens receiving Covid-19 donation by the urban village were carried out offline. These offline activities were held according to health protocols.